2021
DOI: 10.1038/s41598-021-88299-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel multi-strain probiotics reduces Pasteurella multocida induced fowl cholera mortality in broilers

Abstract: Pasteurella multocida causes fowl cholera, a highly contagious poultry disease of global concern, causing significant ecological and economic challenges to the poultry industry each year. This study evaluated the effects of novel multi-strain probiotics consisting of Lactobacillus plantarum, L. fermentum, Pediococcus acidilactici, Enterococcus faecium and Saccharomyces cerevisiae on growth performance, intestinal microbiota, haemato-biochemical parameters and anti-inflammatory properties on broilers experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Although previous studies concentrated on mono-strain probiotics, the application of multi-strain probiotics is gradually now reported by many researchers with mixed outcomes (Abdel-Latif et al, 2018;Olnood et al, 2015a). In a recent study, dietary supplementation with multi-strains probiotic consisting of Lactobacillus fermentum, L. plantarum, Enterococcus faecium, Pediococcus acidilactici and Saccharomyces cerevisiae significantly improved growth performance, some haemato-biochemical parameters as well as beneficially modulating gut microflora and also ameliorating Pasteurella multocida infection in broilers (Reuben et al, 2021). Similarly, Fesseha et al (2021), Ramlucken et al (2020), Kazemi et al (2019) and Olnood et al (2015a) separately reported the effects of multi-strain probiotics supplementation on growth performance, gut microbiome development and diversity, intestinal morphology, lipid oxidation and pathogens control in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies concentrated on mono-strain probiotics, the application of multi-strain probiotics is gradually now reported by many researchers with mixed outcomes (Abdel-Latif et al, 2018;Olnood et al, 2015a). In a recent study, dietary supplementation with multi-strains probiotic consisting of Lactobacillus fermentum, L. plantarum, Enterococcus faecium, Pediococcus acidilactici and Saccharomyces cerevisiae significantly improved growth performance, some haemato-biochemical parameters as well as beneficially modulating gut microflora and also ameliorating Pasteurella multocida infection in broilers (Reuben et al, 2021). Similarly, Fesseha et al (2021), Ramlucken et al (2020), Kazemi et al (2019) and Olnood et al (2015a) separately reported the effects of multi-strain probiotics supplementation on growth performance, gut microbiome development and diversity, intestinal morphology, lipid oxidation and pathogens control in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the transcriptional profiles of anti-inflammatory genes in the intestinal mucosa of probioticfed birds were elevated, haemato-biochemical markers such as packed cell volume, total cholesterol, glucose, proteins, white blood cells, and lymphocytes were also improved. There is a possibility that perhaps the synergy between lactic acid bacteria and yeast strains resulted in higher antimicrobial activity against P. multocida and enterobacteria in the guts of supplemented birds, as well as the ability of the combination to out-compete pathogens, thereby preventing them from attaching to the intestinal walls and as a result improve intestinal microbial balance [95].…”
Section: Multistrain Probiotic Use In Poultrymentioning
confidence: 99%
“…1,140 The findings from several studies revealed that supplementation with probiotics in animals may significantly improve the lipid profile in the blood of ruminants. 141 The supplementation of kids wileyonlinelibrary.com/jsfa or lambs with probiotics was shown to decrease the concentrations of triglycerides, total lipids, low-density lipoproteins and non-esterified fatty acids in the blood of ruminants. 142,143 Panda et al 144 reported a significant reduction in total cholesterol and triglycerides by dietary inclusion of 100 mg kg −1 diet of Lactobacillus sporogenes probiotic in animals.…”
Section: Haemato-biochemical Parameters and Metabolitesmentioning
confidence: 99%
“…The findings from several studies revealed that supplementation with probiotics in animals may significantly improve the lipid profile in the blood of ruminants 141 . The supplementation of kids or lambs with probiotics was shown to decrease the concentrations of triglycerides, total lipids, low‐density lipoproteins and non‐esterified fatty acids in the blood of ruminants 142,143 .…”
Section: Probiotics In Ruminant Nutritionmentioning
confidence: 99%